NATIONAL-EXISTENTIAL TYPE OF THESOURCE IN THE POETRY OF V. STUS, M. VINGRANOVSKY, V. SYMONENKO (Pedagogy of Higher and Secondary Education, 2010)
In the article the essence signs of the artistically expressed national existential type of thesaurus are exposed in a poetry V. Stus, N. Vyngranovskiy, V. Symonenko. The specific of thought is analysed from point of psycholinguistic as deeply national historical understand ing the national existential type of pre-knowledge is outlined in theory to semanentic Ukrainian life .